A STUDY ON EMPLOYEE SATISFACTION OF SUBRAMANIYA SIVA CO-OPERATIVE SUGAR MILLS IN DHARMAPURI DISTRICT - P. Indumathi ,; Dr. S. Deepa, (The journal of contemporary issues in business and government, 2021)
Job satisfaction is an emotional response defining the degree to which people like their job. Work is a central part of almost everyone’s life. It is important that the employees feel a sense of satisfaction with their job or else it might lead to frustration, anger and in some cases even depression. Job satisfaction is also important in everyday life. Organizations have significant effects on the people who work for them and some of those effects are reflected in how people feel about their work. This makes job satisfaction an issue of substantial importance for both employers and employees. The main objectives of this paper is to analyze the socio-economic characteristics, to study the satisfaction level of employees and to find out the several factors influencing job satisfaction of employees in Co-operative sugar mills. Descriptive research design is adopted and hypotheses were formulated based on research objectives. Interview schedule was used for data collection. The data is analyzed using percentage analysis, chi-square and Analysis of Variance.